A Comparative Assessment of Patient Satisfaction and Quality of Life after SMAS Plication vs. Deep Plane Neck Lift - Kamal Uddin Khan, Farzana Abdullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The neck is a vital aesthetic subunit of the face, and neck lift procedures play a crucial role in facial rejuvenation. SMAS (Superficial Musculoaponeurotic System) plication and deep plane neck lift are two established techniques, yet limited data exist comparing their impact on patient satisfaction and postoperative quality of life, especially in the South Asian population. Materials and Methods: This prospective, comparative study was conducted at Bolan Medical Complex, Quetta, from January 2022 to January 2023. Eighty patients were enrolled, with 40 undergoing SMAS plication (Group A) and 40 receiving deep plane neck lift (Group B). Inclusion criteria included age 40–65, ASA class I or II, and primary neck lift candidates. Exclusion criteria included previous neck surgeries, systemic illnesses, and psychiatric disorders. Patient satisfaction was measured using Visual Analog Scale (VAS) and FACE-Q questionnaire. Quality of life was assessed with the WHOQOL-BREF scale preoperatively and at 3 and 6 months postoperatively. Statistical analysis included one-way ANOVA and Pearson correlation (p<0.05). Results: Group B showed significantly higher satisfaction scores (VAS: 8.9 ± 0.8 vs. 7.6 ± 1.0, p<0.001) and improved WHOQOL-BREF scores (75 ± 8 vs. 60 ± 10, p<0.001). One-way ANOVA confirmed statistically significant differences between groups in both satisfaction and quality of life. A moderate positive correlation was observed between VAS and QoL scores (r = 0.34, p = 0.0019). Conclusion: Deep plane neck lift demonstrates greater patient satisfaction and quality of life improvements compared to SMAS plication. Personalized surgical planning and technique selection remain critical to optimizing outcomes. Keywords: SMAS Plication, Deep Plane Neck Lift, Patient Satisfaction, Quality of Life, Aesthetic Surgery, Balochistan.